Meet the press: How voters and politicians respond to newspaper entry and exit - Francesco Drago; Tommaso Nannicini; Francesco Sobbrio (Institute for the Study of Labor (IZA), 2013)
This paper evaluates the effects of changes in the supply of news provided by newspapers on electoral participation, political selection, and government efficiency. We address these issues in the Italian context by constructing a new dataset covering the presence of local news by different types of newspapers (i.e., local and national) for all cities above 15,000 inhabitants in the period 1993-2010. The identification strategy exploits discrete changes in the number of newspapers supplying local news and the precise timing of these events. The results show that the entry of newspapers in the market for local news leads to an increase in turnout in municipal elections, a higher probability of the incumbent mayor being reelected, and an improvement in the efficiency of the municipal government (as measured by the speed of revenue collection). The effect of newspapers on government efficiency is larger when mayors are not term-limited and thus face reelection incentives. Our evidence shows that newspapers do not have a major impact on the selection of politicians, but they play a relevant role in keeping politicians accountable once they are in office. Competition plays a relevant role, as the effects are not limited to the first newspaper entering the market.
Keywords: L82; D72; H70; 330; newspapers; media competition; turnout; political selection; accountability